NFκB inhibition to lift the mechano-competence of mesenchymal stromal cell-derived neocartilage toward articular chondrocyte levels - Lückgen, Janine; Raqué, Elisabeth; Reiner, Tobias; Diederichs, Solvig; Richter, Wiltrud (Stem cell research & therapy, 2022)
Fully functional regeneration of skeletal defects by multipotent progenitor cells requires that differentiating cells gain the specific mechano-competence needed in the target tissue. Using cartilage neogenesis as an example, we asked whether proper phenotypic differentiation of mesenchymal stromal cells (MSC) into chondrocytes in vitro will install the adequate biological mechano-competence of native articular chondrocytes (AC).
Gesehen am 17.05.2022